Changes in availability, utilization, and prices of medicines and protection equipment for COVID-19 in an Urban population of Northern Nigeria - Mainul Haque; Abdullahi Rabiu Abubakar; Olayinka O Ogunleye; Ibrahim Haruna Sani; Israel Sefah; Amanj Kurdi; Salequl Islam; Brian Godman (Wolters Kluwer Medknow Publications, 2021)
Objective: Measures are ongoing to prevent the spread of COVID-19 and treat it with medicines and personal protective equipment (PPE). However, there has been considerable controversy surrounding treatments such as hydroxychloroquine with misinformation fuelling prices hikes and suicides. Shortages have also appreciably increased costs of PPE, potentially catastrophic among lower- and middle-income countries such as Nigeria with high copayment levels. Consequently, a need to investigate changes in availability, utilization, and prices of relevant medicines and PPE during the pandemic in Nigeria. Methods: Exploratory study among community pharmacists with a survey tool comprising four sections including questions on changes in consumption, prices, and shortages of medicines and PPE from the beginning of March 2020 to the end of June 2020. In addition, suggestions from community pharmacists and co-authors on ways to reduce misinformation. Findings: 30 out of 34 pharmacists participated giving a response rate of 88.2%. Significant increases were seen (3-fold or more increase) in the consumption of hydroxychloroquine (100%), vitamins/immune boosters (96.7%) and antibiotics (46.7%) as well as PPE (100%). Considerable price increases (50% increase or greater) also seen for antimalarials (96.7%), antibiotics (93.3%), vitamins/immune boosters (66.7%), and PPE (100%). Shortages are also seen for hydroxychloroquine and vitamins/immune boosters but most severe for PPE (80% of pharmacies). Conclusion: Encouraging to see increases in the utilization of vitamins/immune boosters and PPE. However, a considerable increase in the utilization and prices of antimicrobials is a concern that needs addressing including misinformation. Community pharmacists have a key role in providing evidence-based advice and helping moderate prices.